Teachers' Invisible Presence in Net-based Distance Education - Hult, Agneta; Dahlgren, Ethel; Hamilton, David; Söderström, Tor (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
Conferencing – or dialogue – has always been a core activity in liberal adult education. More recently, attempts have been made to transfer such conversations online in the form of computer-mediated conferencing. This transfer has raised a range of pedagogical questions, most notably “Can established practices be continued? Or must new forms of participation and group management be established? This paper addresses these questions. It is based on two sources: (1) 3,700 online postings from a variety of Net-based adult education courses in Sweden; and (2) interviews with participants and course-leaders. It comprises a discussion of online conversational activity and, in particular, the absent presence and pedagogic orientation of teachers who steer learners towards explicit and implicit course goals. In other words, it is a reminder that adult education is not a free-floating form of self instruction but, rather, operates within boundaries created and managed by other human beings.